The The Relationship Between Genetic Factors and Therapeutic Response in Catastrophic Disease Emergencies: The Relationship Between Genetic Factors and Therapeutic Response in Catastrophic Disease Emergencies - Sari, Sofiani (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2024)
Genetic factors significantly influence therapeutic responses in catastrophic diseases, including myocardial infarction, stroke, and sepsis. Individual genetic variations affect drug metabolism, efficacy, and potential adverse reactions, impacting treatment outcomes. This study aims to analyze the relationship between genetic predisposition and therapeutic response in emergency cases, emphasizing the role of pharmacogenomics in personalized medicine. Data were collected using a retrospective correlational design with 50 patients diagnosed with catastrophic diseases. Pearson's correlation test showed a significant relationship between CYP2C19 polymorphism and antiplatelet therapy effectiveness (r = 0.45, p<0.05), ABCB1 polymorphism and anticoagulant therapy effectiveness (r = 0.38, p<0.05), and TNF-? and IL-6 variations with antibiotic response in sepsis patients (r = 0.32, p<0.05). The integration of pharmacogenomics in emergency treatment can enhance therapeutic effectiveness and reduce adverse effects. However, challenges such as high costs and limited access to genetic testing remain significant barriers. Further research and supportive healthcare policies are essential to optimize the implementation of personalized genetic-based therapy.